Was the German fuel discount passed on to consumers? - Mats Petter Kahl (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2023)
In this article, I analyze whether German gasoline stations passed on the gasoline tax reduction to consumers. I use a difference-in-differences approach with France as the control group, as well as data for all countries in the European Union. The German fuel discount was in effect from June to August 2022. It was intensely debated in the general public whether German gasoline stations had increased prices before the tax reduction. Such a price increase would have made it easier for gasoline stations to disguise a price increase. Further questions follow: How long did it take for the full tax reduction to be passed on to consumers? Did gasoline stations reduce the pass-on after a few weeks? As I am the first to use complete French and German high-frequency data for the entire treatment period, I can examine how the pass-through of the tax cut evolved over time. I find substantial variance in pass-through rates over time. The average pass-through is very high but remains incomplete for all fuel types.
Keywords: H22; L13; L41; 330; pass-through; gasoline market; tax reduction; fuel taxes; petrol prices